Discursive Developments of Qur’anic Exegesis within the Indonesian Pesantren Tradition: A Bibliometric Analysis - Idris, Haidar; Fajarudin, Akhmad Afnan (Pesantren and Community Development Studies - Islamic Institute of Syarifuddin, Indonesia., 2025)
This study offers a comprehensive bibliometric analysis of Qur’anic exegesis (tafsir) within the Indonesian pesantren (Islamic boarding school) tradition over the past twenty-five years (2000–2025). Employing a Systematic Literature Review (SLR) and bibliometric mapping tools such as VOSviewer, the research identifies key themes, dominant methodological trends, and critical research gaps in this field. The results reveal that while pesantren hold a pivotal role in preserving and transmitting tafsir knowledge, scholarly attention to systematic studies in this area remains limited. Predominant research themes include Islamic education, civil society engagement, multicultural pedagogy, religious networks, and the socio-political role of tafsir. Methodologically, studies tend to lean on narrative and descriptive approaches, with limited quantitative or systematic review methodologies explicitly employed. This study bridges that gap by offering a conceptual synthesis and providing a thematic and network-based visualization of the field. The research contributes both to academic discourse by mapping the epistemic and thematic landscape of tafsir in pesantren, and to practical policy by offering insights that could inform curriculum development, pedagogical innovation, and future interdisciplinary research directions.